Spontaneous-emission-induced ratchet in atom-optics kicked-rotor quantum walks - Bolik, Nikolai; Wimberger, Sandro (Physical review, 2024)
Quantum walks have gained significant attention over the past decades, mainly because of their variety of implementations and applications. Atomic quantum walks are typically subject to spontaneous emissions arising from the control fields. We investigate spontaneous emission in an atom-optics kicked-rotor quantum walk. Here, spontaneous emission occurs naturally due to the driving by the kicks, and it is generally viewed as a nuisance in the experiment. We find, however, that spontaneous emission may induce asymmetries in an otherwise symmetric quantum walk. Our results underscore the utility of spontaneous emission and the application of the asymmetric evolution in the walker's space, i.e., for the construction of a quantum walk ratchet or for Parrondo-like quantum games. This highlights the potential for reinterpreting seemingly adverse effects as beneficial under certain conditions, thus broadening the scope of quantum walks and their applications.
Gesehen am 28.10.2024